A Preliminary Risk Assessment Protocol for Renegade Nanoparticles Deployed During Nanoremediation. Issue 3 (June 2016) - Nathanail, C. Paul; Gillett, Andy; McCaffrey, Caroline; Nathanail, Judith; Ogden, Richard
Abstract : The NanoRem European research project aims to support and develop the appropriate use of nanotechnology for contaminated land remediation by facilitating practical, economic, and exploitable nanotechnology for in situ remediation. This can only be achieved in parallel with a comprehensive understanding of the environmental risk‐benefit balance for the use of the nanoparticles (NPs) being investigated. While the NanoRem NPs could have a significant toxicity this is likely to be less potent than NPs currently being released into the environment, such as those from a variety of antibacterial products. The NanoRem NPs are likely to interact with the aquifer matrix, each other, and groundwater chemistry to rapidly cease to be mobile and are unlikely to penetrate into the aquifer more than a few meters from the point of injection. In terms of the source‐pathway‐receptor paradigm, the NanoRem NPs are cautiously presumed to represent a hazard (i.e., source). At least one receptor, in the form of not yet polluted groundwater, is present at all the NanoRem case study sites. While there are considerable uncertainties particularly with regards to the transport of NanoRem NPs, the ability of NPs to penetrate far into the formation is likely to be very limited. The relatively short travel distances reported in the literature for a variety of NP types and geological conditions suggest that the pathways are at best very limited in extent. Overall, this means that in many cases the level of risk renegade NPs can pose to the environment or human health is at most minimal. A qualitative protocol developed for the NanoRem field trials can demonstrate that injecting NanoRem NPs into contaminated groundwater poses a minimal level of risk due to the reduced pathway. ©2016 Wiley Periodicals, Inc.